2016
DOI: 10.1080/17565529.2016.1146118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating capacity for climate change adaptation in the health and water sectors in Vietnam: constraints and opportunities

Abstract: The capacity to anticipate and respond to climate change can critically shape vulnerability, influencing whether a country experiences harm from exposure to stresses or is able to cope, adapt and realize sustainable outcomes. This paper presents the results of a study that evaluates capacity in relation to the health and water sectors in Vietnam. The study presents informants' views on the adequacy of financial resources, understanding of vulnerability and adaptation, training needs, information requirements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…These actions can be classified in the "stand-alone adaptation", "adaptation plus development" in Ayers and Dodman's categories [48]. This finding is consistent with other adaptation studies in Vietnam that highlight the limited attention paid to soft measures, especially at the provincial and lower levels [56], and to improve the local adaptive capacities [63]. Mc Elwee [36] argues that, in Vietnam, those capacities are closely linked to the access to social capital, collective action, common lands, institutional support, and government safety nets.…”
Section: Development or Adaptation Finance?supporting
confidence: 85%
“…These actions can be classified in the "stand-alone adaptation", "adaptation plus development" in Ayers and Dodman's categories [48]. This finding is consistent with other adaptation studies in Vietnam that highlight the limited attention paid to soft measures, especially at the provincial and lower levels [56], and to improve the local adaptive capacities [63]. Mc Elwee [36] argues that, in Vietnam, those capacities are closely linked to the access to social capital, collective action, common lands, institutional support, and government safety nets.…”
Section: Development or Adaptation Finance?supporting
confidence: 85%
“…Regional water demand is also sensitive to climate change [26][27][28]. It is generally suggested that climate change will trigger more water demand [7,9,10]. rough reviewing the related literature [24,25], the paper assumes that the effect of temperature rise on water demand is defined as Wate t � 1 + 0.05T + 0.01T 2 Wate t , (27) where Wate t represents the regional water demand in period t, T represents this period's climate anomaly, and Wate t denotes the regional water in period t in the absence of climate warming.…”
Section: 22mentioning
confidence: 99%
“…ese climate change impact and risk may also restrict human life in many aspects [7]. Climate change adaptation aims to reduce or manage the impact of climate change on people's lives, which is bound to increase regional demand for electricity [8], water [9,10], and health services [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive capacity is context specific, meaning there is no single set of indicators of adaptive capacity applicable to every setting, and indicators must be tailored to each case [20,24]. A plethora of adaptive capacity indicators have been proposed, including: economic resources, technology, information and skills, infrastructure, institutions, equity, priorities, kinship networks and political influence [16,23,[25][26][27]. Drawing on this literature, we selected dimensions of adaptive capacity over which upper-level governments could have some influence, and that were most applicable to the context of local public health authorities (as opposed to, for example, countries, communities or individuals).…”
Section: Conceptual Frameworkmentioning
confidence: 99%